(untitled) (Revista de Artes Marciales Asiáticas, 2013)
The present article deals with an analysis of an undated Persian archery manuscript titled Resale-ye Kamandari [Archery Manuscript] written by Kapur Cand. It is written in Persian and judging by the style it should have been written by a Persian. Persian archery manuscripts provide useful information on the usage of a contemporary Persian composite bow. First the article describes where the archery manuscript was found and collected. Then it describes the qualities of an archer in ten points. The next part of the article presents the characteristics of a Persian composite bow as described in the manuscript. Then the article discusses the suggested materials for making a bowstring. The next part of the manuscript deals with the materials used for making an arrow and useful information in the manuscript for bracing a Persian bow. The final part of the article explains different shooting techniques that can be used in shooting with a Persian composite bow.